2019
DOI: 10.1177/1367493519831493
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy, nutrition knowledge, and health care transition readiness in youth with chronic kidney disease or hypertension: A cross-sectional study

Abstract: This study evaluates the associations of nutrition knowledge and health literacy with health care transition (HCT) readiness and self-management in adolescents and young adults (AYAs) with chronic kidney disease (CKD) or hypertension. Chronically ill AYAs with poor HCT or self-management skills are less likely to achieve favorable health outcomes as they enter adulthood. Health literacy and nutrition knowledge, which are identified as important contributors to health outcomes, may suggest important points of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…Overall, 6 of the 11 studies described significant correlations between health literacy and considered outcomes comprising four of eight categories designed by Sørensen et al ( Table 4 ) [ 52 , 55 , 57 , 58 , 59 , 60 ]. Regarding health behavior, one of three studies on health behaviour had data showing significant associations between health literacy and self-management in an underaged population with chronic kidney disease.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 6 of the 11 studies described significant correlations between health literacy and considered outcomes comprising four of eight categories designed by Sørensen et al ( Table 4 ) [ 52 , 55 , 57 , 58 , 59 , 60 ]. Regarding health behavior, one of three studies on health behaviour had data showing significant associations between health literacy and self-management in an underaged population with chronic kidney disease.…”
Section: Resultsmentioning
confidence: 99%
“…LHL was associated with worse control of blood pressure [ 55 , 61 ], lower medication adherence confidence [ 44 , 53 ] and lower quality of life [ 56 ]. For worse treatment and self-care knowledge [ 7 , 41–43 , 49 , 52 , 53 , 79 ], worse self-care behaviours [ 7 , 40 , 43 , 51 , 55 ], including lifestyle [ 40 , 50 , 51 ] and adherence problems [ 8 , 38 , 46 , 51 , 53 ] some studies found an association with LHL, while others did not. LHL was not associated with CKD awareness [ 33 , 47 ], treatment preferences [ 67 ], disaster preparedness [ 57 ] and phosphate regulation [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…CKD patients did not perceive engaging with providers as their greatest HL problem [ 37 , 42 , 45 ]. However, in adolescents ˃18 years, one study showed that LHL was associated with several behaviours related to communication [ 43 ]. Another study showed an association of these behaviours with perceived general health [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Obesity and obesity-related hypertension are increasing in adolescents, which can lead to cardiovascular events and CKD earlier in adult life. At the point of transition, these at-risk patients should be recognized, followed up, and treated before complications develop [ 42 , 43 , 44 ]. Patients with urinary incontinence are also a neglected group of adolescents that very often receive suboptimal care in adult life.…”
Section: Discussionmentioning
confidence: 99%